ANALISIS PENGARUH FAKTOR-FAKTOR PRODUKSI TERHADAP PRODUKSI PADI ANGGOTA KELOMPOK TANI MARGO UTOMO KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Melati Hutahaean; B. M. Setiawan; E. Prasetyo (Agroland: Jurnal Ilmu-ilmu Pertanian, 2019)
This study aimed to analyze the effect of utilizing production factors on rice production and to analyze the level of economic efficiency and technical efficiency of using production factors in rice farming system of the members of the Margo Utomo farmer group in Kalikayen village, Ungaran Timur sub-district, Semarang district. This research was conducted in November - December 2018 and the location was determined purposively in Kalikayen village, Ungaran Timur sub-district, Semarang district. Determination of samples in this study used the census method. Data was collected from all members of the Margo Utomo farmer group of 50 respondents by interviews using questionnaires. The data was analyzed using the multiple linear regression analysis method which than transformed into the Cobb-Douglas model production function and using one sample t-test to find the technical efficiency and the economic efficiency. The results showed that the use of production factors of land, seed, urea fertilizer had significant effect on the rice yield while the production factors of labor and pesticide had no effect. The use of factors such as land, labor, seed, urea fertilizer and pesticide was technically inefficient. The use of production factors such as land, seed, and urea fertilizer was not yet economically efficient while labor and pesticide was economically inefficient.Keywords : Efficiency, Factors Of Production, and Rice Production.